Perception and belief of dietary intake among newly diagnosed with gynaecologic cancer in Malaysia: a qualitative study - Yi Ho, Chiou; Mat Daud, Zulfitri Azuan; Mohd Yusof, Barakatun Nisak; Abdul Majid, Hazreen (EpiSmart Science Vector Ltd, 2024)
Background: Gynaecologic cancers (GC) experience unintentional weight loss and inadequate oral intake even before treatment. Cancer patients are at risk of accessing inaccurate advice and misleading information due to the prevalence of misinformation regarding nutrition and cancer in the media. This study aimed to obtain a comprehensive understanding of the perception and belief of dietary intake among newly diagnosed with GC in Malaysia. Methods: We conducted in-depth qualitative interviews with 12 GC respondents from three major ethnicities and continued until the saturation point was reached. A semi-structured interview guide is employed. The interviews were audio recorded and verbally transcribed. Thematic analysis with theoretical saturation was applied to data analysis. Results: The majority of patients interviewed reported that they made dietary modifications following their GC diagnosis, such as healthy eating, and began taking supplements. Their belief and perception of dietary intake were influenced by the impact of diagnosis, uncertainty, and fear of cancer progression and empowerment through nutrition. The cultural influence and access to resources and information might affect their dietary intake. There was evidence of navigating information overload from various sources after newly diagnosed GC. They felt a dilemma in food choices, balancing emotional and nutritional needs. The multidisciplinary support systems and healthcare delivery approach were useful. Discussion and conclusion: The perception and belief of dietary intake among newly diagnosed with GC in Malaysia is diverse and can vary greatly depending on individual experiences, beliefs, and situations. They may attempt to restore some control over their health in the face of a cancer diagnosis. All respondents admitted that they changed to a healthy diet after being diagnosed with GC. The healthcare profession might benefit from current qualitative research to better understand more patients and increase the quality of oncology dietetic service and decision-making. Hence, effective dietary interventions and support strategies could be established for this population.